Šliogerio ir Heideggerio hominizuotos būties sampratos skirtumai jų meno filosofijose. - Kavaliauskas, Tomas (Problems / Problemos, 2023)
Two different philosophical attitudes towards the hominized Being are analyzed: the one of Arvydas Šliogeris and the other of Martin Heidegger. The aim is to show the philosophy of Being in relation to particular paintings. Šliogeris interprets the picture of The Great Pine Tree by Paul Cézanne, whereas Heidegger - the picture of A Pair of Shoes by Vincent van Gogh. The author of the article explains how Aristotle's concept of the individual substance is related to the art philosophy of Šliogeris. The article also shows how Šliogeris' critique of the hominized Being consistently evolved starting with his book The Thing and Art and culminating with his major work, titled The Silence of Transcendence. At the end of the article the author brings to the reader's attention two self-contradictory notions of an artist that we find in different books of Šliogeris: the first notion that speaks of a Human-artist who supposedly imbues 'more Being' into a painting than we find it in nature; whereas the second notion speaks of a Nature-artist and provides to things 'more Being' than we find it in art.